Effects of ascorbic acid and erythorbic acid on melanosis and quality in different shrimp species - Toktas, Bulent; Gokoglu, Nalan (Acta Aquatica: Aquatic Sciences Journal, 2020)
With this study, ascorbic acid and erythorbic acid were used for the first time to prevent melanosis in shrimp. Three shrimp species (Aristaeomorpha foliacea, Plesionika edwardsi and Melicertus hathor) were used. It was determined that melanosis scores were higher in the control groups. Combination of ascorbic acid and erythorbic acid with metabisulphite was found to be more effective in inhibiting of melanosis than the application alone. No significant differences were found between the groups in terms of TVB-N values. The TMA-N value of the control group was significantly higher than those of application groups. Ascorbic acid, Erythorbic acid and their combinations with sodium metabisulphite were found effective on inhibition of melanosis and quality changes in three shrimp species.Keywords: reducing agents; ascorbic acid; erythorbic acid; melanosis; quality; shrimp